2022
DOI: 10.3390/ijerph192113968
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Cultural Ecosystem Services Value of Protected Areas Considering Stakeholders’ Preferences and Trade-Offs—Taking the Xin’an River Landscape Corridor Scenic Area as an Example

Abstract: Improving the accuracy of cultural ecosystem services (CESs) value assessment and paying more attention to the preferences and trade-offs of stakeholders in the administration of CESs are of vital importance for achieving resilient ecosystem management. Combining methodologies from sociology (Q method) and economics (choice experiment), an assessment framework of CESs is introduced to examine stakeholders’ preferences and willingness to pay to participate in CESs in protected areas so as to explore how the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Simultaneously, to bolster the connectivity of urban river corridors, optimizing public transportation routes and installing bike lanes are necessary measures to enhance user mobility. Through the collaborative efforts of government departments, urban planners, community organizations, and the public, a more pleasant, convenient, and sustainable environment for urban river corridors can be created, providing residents and tourists with enhanced leisure experiences [139,140].…”
Section: Insights Into Urban River Corridor Managementmentioning
confidence: 99%
“…Simultaneously, to bolster the connectivity of urban river corridors, optimizing public transportation routes and installing bike lanes are necessary measures to enhance user mobility. Through the collaborative efforts of government departments, urban planners, community organizations, and the public, a more pleasant, convenient, and sustainable environment for urban river corridors can be created, providing residents and tourists with enhanced leisure experiences [139,140].…”
Section: Insights Into Urban River Corridor Managementmentioning
confidence: 99%
“…We have found that heterogeneity in the perception of heritage destination CESs is quite complex, with differences in user identity and attitudes influencing the extent to which the landscape environment is perceived [32]. Previous studies have focused on tourists [33,34] and ignored the critical role of residents [35]. Residents living within the service radius of a national cultural park are the primary users.…”
Section: Introductionmentioning
confidence: 96%